2021
DOI: 10.1177/26335565211002402
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability of nurse-led reviews for inflammatory rheumatological conditions: A qualitative study

Abstract: Background: People with inflammatory rheumatological conditions (IRCs), are at increased risk of comorbidities such as cardiovascular disease, osteoporosis, anxiety and depression. The INCLUDE pilot trial evaluated a nurse-delivered review of people with IRCs which sought to identify and initiate management of comorbid conditions. Aim: A nested qualitative study was undertaken to examine the acceptability of the INCLUDE review. Methods: A qualitative interview-based design in UK primary care settings. A purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…(eight and seven interviews, respectively). The interview guide (Supporting Information: Appendix S1 ) was developed using a systematic process recommended in theory‐informed qualitative research 14 and informed by the TFA (explained further in the section on ‘Rigor’ below). The interview topic guide was designed to explore the seven constructs of the TFA.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(eight and seven interviews, respectively). The interview guide (Supporting Information: Appendix S1 ) was developed using a systematic process recommended in theory‐informed qualitative research 14 and informed by the TFA (explained further in the section on ‘Rigor’ below). The interview topic guide was designed to explore the seven constructs of the TFA.…”
Section: Methodsmentioning
confidence: 99%
“…The TFA comprises seven constructs 13 (Table 1 presents TFA constructs and definitions). The TFA has been used successfully in other (nonsurgical) contexts to identify components that could be addressed to enhance acceptability, such as nurse‐led reviews of inflammatory rheumatological conditions, postnatal exercise and infant feeding practices 14–16 . It has also been applied in a small number of surgical contexts such as maternal–foetal surgery and intravitreal injections for macular degeneration 17,18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived effectiveness was conceptualised a ‘secondary domain’ meaning that patients’ perceived effectiveness of remote consulting was dependant on their perceptions of self-efficacy, ethicality, burden and opportunity costs. In previous qualitative research using the TFA, we also identified affective attitudes and intervention coherence as ‘secondary domains’ [ 18 , 31 ]. The TFA has been criticised for excluding social and environmental factors [ 32 , 33 ], although we were able to incorporate wider macro and meso level influences into our model (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This study used the Theoretical Framework of Acceptability (TFA) [ 17 ], developed to inform the understanding of acceptability of complex interventions (defined for our context as a remote consultation), and consists of seven constructs (Table 2 ), and previously used to explore the acceptability of consultations [ 18 ].…”
Section: Methodsmentioning
confidence: 99%